2015
DOI: 10.1371/journal.pone.0135582
|View full text |Cite
|
Sign up to set email alerts
|

High Inorganic Phosphate Intake Promotes Tumorigenesis at Early Stages in a Mouse Model of Lung Cancer

Abstract: Inorganic phosphate (Pi) is required by all living organisms for the development of organs such as bone, muscle, brain, and lungs, regulating the expression of several critical genes as well as signal transduction. However, little is known about the effects of prolonged dietary Pi consumption on lung cancer progression. This study investigated the effects of a high-phosphate diet (HPD) in a mouse model of adenocarcinoma. K-rasLA1 mice were fed a normal diet (0.3% Pi) or an HPD (1% Pi) for 1, 2, or 4 months. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Studies in mice have suggested positive correlations between high serum Pi and cancer. [19][20][21] In the JB6 mouse model, a high Pi diet resulted in cell transformation and skin tumorigenesis by stimulating N-Ras and downstream ERK1/2 phosphorylation. 19 In K-ras LA1 mice, elevated Pi promoted lung cancer progression at an early stage by stimulating cell proliferation and angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in mice have suggested positive correlations between high serum Pi and cancer. [19][20][21] In the JB6 mouse model, a high Pi diet resulted in cell transformation and skin tumorigenesis by stimulating N-Ras and downstream ERK1/2 phosphorylation. 19 In K-ras LA1 mice, elevated Pi promoted lung cancer progression at an early stage by stimulating cell proliferation and angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Pi has been identified as an essential nutrient for cell growth(Chang et al, 2006, Conrads et al, 2005) and proliferation(Roussanne et al, 2001). Its potential roles in tumor development have been implicated in in cancers of breast(Lin, McKinnon et al, 2015), lung(Jin et al, 2009, Lee et al, 2015), skin(Camalier et al, 2010) and kidney(Brown & Razzaque, 2018). Paradoxically, lines of evidence also demonstrate Pi overload has systematically detrimental effects such as cardiovascular disorders(Tonelli et al, 2005) and renal dysfunction(Marks et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In JB6 mice model, a high Pi diet resulted in cell transformation and skin tumorigenesis by stimulating N-Ras and downstream ERK1/2 phosphorylation(Jin et al, 2009). In K-ras LA1 mice, elevated Pi promoted lung cancer progression at early stage by stimulating cell proliferation and angiogenesis(Lee et al, 2015). On the other hand, evidence also showed Pi’s toxic effects of triggering cell death(Di Marco, Hausberg et al, 2008) and tissue damage(Nakatani, Sarraj et al, 2009, Yoshikawa, Yamamoto et al, 2018, Zhang, Yang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This result suggests that a standard soda drink can even influence individuals with normal renal function (24). Moreover, dietary phosphorus overload may be related to various kinds of malignancies such as lung, breast and prostate cancers, since phosphorus burden influences cancer cell growth and metabolism (3,25,26). However, the results of earlier studies have not always been consistent and further research is needed to clarify the underlying molecular connections.…”
Section: Possible Effects Of Carbonated Drinks On Healthy Adults Withmentioning
confidence: 99%